VD_FINDINFO AP / 2009 / 25 vom 5. Mai 2008 - VD Tribunal cantonal (2008)
MAXIME DES DÉBATS, MAXIME DE DISPOSITION, FORMALISME EXCESSIF | 3 CPC, 4 al. 1 CPC, 4 al. 2 CPC, 444 al. 1 ch. 3 CPC, 444 CPC, 83 al. 2 LP, 83 LP